Early Elevated Troponin Levels After Ischemic Stroke Suggests a Cardioembolic Source. Issue 1 (January 2018) - Yaghi, Shadi; Chang, Andrew D.; Ricci, Brittany A.; Jayaraman, Mahesh V.; McTaggart, Ryan A.; Hemendinger, Morgan; Narwal, Priya; Dakay, Katarina; Mac Grory, Brian; Cutting, Shawna M.; Burton, Tina M.; Song, Christopher; et al.
Abstract : Background and Purpose—: Elevated cardiac troponin is a marker of cardiac disease and has been recently shown to be associated with embolic stroke risk. We hypothesize that early elevated troponin levels in the acute stroke setting are more prevalent in patients with embolic stroke subtypes (cardioembolic and embolic stroke of unknown source) as opposed to noncardioembolic subtypes (large-vessel disease, small-vessel disease, and other). Methods—: We abstracted data from our prospective ischemic stroke database and included all patients with ischemic stroke during an 18-month period. Per our laboratory, we defined positive troponin as ≥0.1 ng/mL and intermediate as ≥0.06 ng/mL and <0.1 ng/mL. Unadjusted and adjusted regression models were built to determine the association between stroke subtype (embolic stroke of unknown source and cardioembolic subtypes) and positive and intermediate troponin levels, adjusting for key confounders, including demographics (age and sex), clinical characteristics (hypertension, hyperlipidemia, diabetes mellitus, renal function, coronary heart disease, congestive heart failure, current smoking, and National Institutes of Health Stroke Scale score), cardiac variables (left atrial diameter, wall-motion abnormalities, ejection fraction, and PR interval on ECG), and insular involvement of infarct. Results—: We identified 1234 patients, of whom 1129 had admission troponin levels available; 10.0% (113/1129) of these had a positive troponin. In fully adjusted models, there was an association between troponin positivity and embolic stroke of unknown source subtype (adjusted odds ratio, 4.46; 95% confidence interval, 1.03–7.97; P =0.003) and cardioembolic stroke subtype (odds ratio, 5.00; 95% confidence interval, 1.83–13.63; P =0.002). Conclusions—: We found that early positive troponin after ischemic stroke may be independently associated with a cardiac embolic source. Future studies are needed to confirm our findings using high-sensitivity troponin assays and to test optimal secondary prevention strategies in patients with embolic stroke of unknown source and positive troponin.